Edukasi Keluarga Sakinah sebagai Upaya Penguatan Ketahanan Keluarga Masyarakat Kota Medan: Kolaborasi Perguruan Tinggi dan Kementerian Agama - Hairun Hasanah Sagala; Bahatma Baca; Muhari Syahlaili Saragih; Putri Sabrina (Indo Publishing, 2026)
This community service activity aims to increase public understanding of the concept of a harmonious family as an effort to strengthen family resilience in Medan City. The activity was implemented through an educational-participatory approach in the form of a public campaign involving the Medan City Ministry of Religious Affairs, the Medan City Government, and the Faculty of Islamic Studies, Nahdlatul Ulama University, North Sumatra. The target audience was the general public participating in the educational activity at Merdeka Square, Medan City. The implementation methods used included observation, documentation, and direct participation in the harmonious family education activities. The results showed that the harmonious family education program was able to raise public awareness of the importance of legal marriage, effective family communication, and strengthening religious values in domestic life. Furthermore, this activity also strengthened the synergy between universities, the government, and the community in supporting the family resilience strengthening program. Thus, this community service activity made a positive contribution to building public understanding of the harmonious family and supporting the creation of harmonious and resilient families in Medan City.